Prescription Writing Errors in Clinical Clerkship among Medical Students - Indriyanti, Raden Anita; Yulianto, Fajar Awalia; Andriane, Yuke (Global Medical & Health Communication (GMHC), 2019)
Prescription is an instruction written by a medical practitioner to give a drug or device for a patient. The proper prescription will contribute to speedy recovery or healing process for the patient. Clinical clerkship must have an excellent competency to choose the right medication and prescribe the appropriate drugs or therapy. This study aims to analyze the common error in prescription's writing in clinical clerkship among medical students at their final examination to be a medical doctor. This study used the analytic method to 609 sheets of prescription from 180 clerkship students in their last try out on objective structured clinical examination (OSCE) at the Faculty of Medicine Universitas Islam Bandung in March 2018. Analyzed the component that every prescription should have, which consists of patient identity, superscription, inscription, subscription, and signatures. The result showed that more than half of the clerkship students made an error in subscription (50.25%) and signatures items (55.83%), while most of them had written down properly the patient identity (77.5%), superscription (83.74%), and inscription (78.98%). As a result, with more than half error in a prescription written in subscription and signature item, the failure of giving adequate therapy will cause a low recovery or healing process to the patients. Moreover, it may harm or cause death to the patients. In conclusion, more than half of medical students made common errors in prescription's writing. KESALAHAN PENULISAN RESEP PADA MAHASISWA KOASISTENSI FAKULTAS KEDOKTERANResep merupakan instruksi yang ditulis oleh tenaga medis untuk memberikan obat atau seperangkat alat kepada pasien. Peresepan yang tepat akan membawa proses pemulihan dan penyembuhan terhadap pasien. Mahasiswa kedokteran yang menjalankan masa koasisten harus memiliki kompetensi yang baik untuk memilih dan menuliskan terapi yang sesuai. Penelitian ini bertujuan menganalisis kesalahan umum dalam penulisan resep pada mahasiswa kedokteran yang akan menghadapi ujian akhir untuk menjadi seorang dokter. Penelitian ini menggunakan metode analitik terhadap 609 lembar resep dari 180 mahasiswa kedokteran yang sedang melaksanakan try out akhir objective structured clinical examination (OSCE) di Fakultas Kedokteran Universitas Islam Bandung pada Maret 2018. Dianalisis setiap komponen yang harus ada dalam penulisan resep, yaitu identitas pasien, superskripsi, inskripsi, subskripsi, dan signature. Hasil penelitian menunjukkan bahwa lebih dari setengah mahasiswa melakukan kesalahan pada item subskripsi (50,25%) dan signature (55,83%), sedangkan sebagian besar sudah menulis dengan baik pada item identitas pasien (77,5%), superskripsi (83,74%), dan inskripsi (78,98%). Akibatnya, dengan lebih dari setengah jumlah kesalahan dalam penulisan item subskripsi dan signature maka kegagalan dalam memberikan terapi yang adekuat dapat menyebabkan angka kesembuhan yang rendah, terlebih lagi dapat menimbulkan bahaya bahkan kematian terhadap pasien. Simpulan, lebih dari setengah mahasiswa kedokteran melakukan kesalahan umum dalam penulisan resep.